Loss of a conserved salt bridge in bacterial glycosyl hydrolase BgIM-G1 improves substrate binding in temperate environments. (December 2018) - Mhaindarkar, Dipali; Gasper, Raphael; Lupilov, Natalie; Hofmann, Eckhard; Leichert, Lars
Abstract Salt bridges are the strongest electrostatic interactions in proteins. They substantially contribute to a protein's structural stability. Thus, mutations of salt bridges are typically selected against. Here, we report on the evolutionary loss of a highly conserved salt bridge in the GH1 family glycosyl hydrolase BglM-G1. BglM-G1's gene was found in the bacterial metagenome of a temperate, seasonally cold marine habitat. In BglM-G1, arginine 75 is replaced by a histidine. While fully retaining β-glucosidase activity, BglM-G1 is less heat stable than an H75R variant, in which the salt bridge was artificially re-introduced. However, theK m toward its substrates was lower in wild type, leading to an overall higher catalytic efficiency. Our results indicate that this loss of the salt bridge leads to higher flexibility in BglM-G1's active site, trading structural stability at high temperatures, a trait not needed in a temperate, seasonally cold habitat, for a more effective catalytic activity. Dipali Mhaindarkar et al. examine the functional effects of a salt bridge loss in the active site of glycosyl hydrolase Bg1M-G1, found in the metagenome of a seasonally cold marine habitat. They show that the catalytic efficiency is overall higher with the lost salt bridge, trading off with lower thermal stability.